Disseminated vaccine-strain varicella-zoster virus reactivation in an adolescent with secondary immunodeficiency: a case report and literature review - Fashina, Oluwatomini A.; Chuang, Tony M.; Galardy, Paul J.; Huskins, W. Charles; Levy, Emily R.; Streck, Nicholas T.; Chakraborty, Rana (BMC infectious diseases, 2024)
Routine childhood immunization against varicella-zoster virus has led to a dramatic reduction in the incidence of primary varicella. However, there are rare, yet significant cases reported of reactivated Oka-strain varicella, primarily in immunocompromised hosts. A 16-year-old female with Hodgkin's lymphoma developed a vesicular rash shortly after completing all chemotherapy treatment. Swabs obtained from the vesicles were positive for varicella-zoster virus. By the time of hospitalization, the patient developed a disseminated rash involving multiple dermatomes. Subsequent polymerase chain reaction confirmed Oka vaccine-strain varicella-zoster virus. The patient had previously received a primary series of immunizations against varicella in 2008 and 2012, with her 2nd dose given 11 years prior to her development of vaccine-strain herpes zoster and 10 years prior to her diagnosis of Hodgkin's lymphoma, respectively. The patient was treated with parenteral acyclovir upon hospitalization and monitored clinically for cutaneous disease progression as well as sequelae. After 8 days of inpatient treatment, her rash had stopped spreading with no new lesions. All earlier lesions had crusted over. No serious sequelae of disease such as pneumonitis, hepatitis, encephalitis, or meningitis occurred, and she made a complete recovery. There are individual and community-wide benefits to childhood immunization against varicella. This case highlights an unusual presentation of disseminated vaccine-strain herpes zoster in an adolescent with secondary immunodeficiency 11 years after completing primary immunization. In addition, this case informs pediatricians of complications that can arise in immunized subjects if they become immunosuppressed years later. The only way to distinguish between wild-type and vaccine-strain herpes zoster was by viral genotyping. Providers should be cognizant of potential vaccine virus reactivation in their differential. Considerations for work-up and management should include infection control and viral resistance in refractory cases.